DL‐3‐n‐butylphthalide suppressed autophagy and promoted angiogenesis in rats with vascular dementia by activating the Shh/Ptch1 signaling pathway. (20th November 2021) - Niu, Xiaoli; Li, Meixi; Gao, Yaran; Xu, Guodong; Dong, Xiaoli; Chu, Bao; Lv, Peiyuan
Highlights: DL-3-n-butylphthalide (NBP) attenuated memory and neuronal damage in VD rats. NBP decreased autophagy and promoted angiogenesis in VD rats. NBP exerted neuroprotective effects by activating the Shh/Ptch1 signaling pathway. Abstract: DL-3-n-butylphthalide (NBP) has neuroprotective effect on chronic cerebral hypoperfusion animals. Here, we explored the role and underlying mechanism of NBP on autophagy and angiogenesis in rats with vascular dementia (VD). Adult male Sprague-Dawley (SD) rats were subjected to permanent bilateral occlusion of the common carotid arteries (2VO) to establish VD model. These rats were randomly divided into five groups: sham, model, NBP120 (120 mg/kg), Shh siRNA (50 nM), and NBP120  + Shh siRNA groups. Our results showed that NBP treatment attenuated memory damage in rats with VD, as demonstrated by Morris water maze tests. Immunofluorescence (IF) assay revealed that NBP induced neuronal process length and neuronal activity in hippocampus, which were reversed by Shh silencing. Furthermore, NBP treatment also reduced the expression of autophagy marker proteins B-cell lymphoma-2 interacting protein 1 (Beclin 1) and microtubule-associated protein 1 light chain 3 (LC3), which were further enhanced by Shh silencing. Meanwhile, NBP promoted the angiogenesis, which was accompanied by upregulated vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF)-1, and Angiopoietin (Ang) expression in the hippocampus. And Shh siRNA co-treatment blocked the angiogenesis induced by NBP. Altogether, our results established that NBP treatment suppressed autophagy and improved angiogenesis and neurobehavioral recovery in VD rats partly by activating the Shh/Ptch1 signaling pathway.